The early phase influence of bone marrow concentrate on metaphyseal bone healing - Jungbluth, Pascal; Hakimi, A. R.; Grassmann, J. P.; Schneppendahl, J.; Kroepil, P.; Thelen, S.; Sager, M.; Herten, Monika; Wild, M.; Windolf, J.; Hakimi, M.; Betsch, Marcel (Injury-International Journal of the Care of the Injured, 2013)
Bone marrow concentrate (BMC) contains high densities of progenitor cells. Therefore, in critical size defects BMC may have the potency to support bone healing. The aim of this study was to investigate the effect of BMC in combination with calcium phosphate granules (CPG) on bone defect healing in a metaphyseal long bone defect in mini-pigs. A metaphyseal critical-size bone defect at the proximal tibia of 24 mini-pigs was filled with CPG combined with BMC, CPG solely (control group) or with an autograft. Radiological and histomorphometrical evaluations after 6 weeks (42 days) showed significantly more bone formation in the BMC group in the central area of the defect zone and the cortical defect zone compared to the CPG group. At the same time the resorption rate of CPG increased significantly in the BMC group. Nevertheless, compared to the BMC group the autograft group showed a significantly higher new bone formation radiologically and histomorphometrically. In BMC the count of mononuclear cells was significantly higher compared to the bone marrow aspirate (3.5-fold). The mesenchymal progenitor cell characteristics of the cells in BMC were confirmed by flow cytometry. Cells from BMC created significantly larger colonies of alkaline phosphatase-positive colony forming units (CFU-ALP) (4.4-fold) compared to cells from bone marrow aspirate. Nevertheless, even in the BMC group complete osseous bridging was only detectable in isolated instances of the bone defects. Within the limitations of this study the BMC + CPG composite promotes bone regeneration in the early phase of bone healing significantly better than the isolated application of CPG. However, the addition of BMC does not lead to a solid fusion of the defect in the early phase of bone healing an still does not represent an equal alternative to autologous bone. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Animal model; Bone defect; Bone marrow concentrate; Calcium phosphate granules; Colony forming units; Growth factors